Leaving everything most loved ebook - Winspear, Jacqueline (Maisie Dobbs, 2013)
In Leaving Everything Most Loved by New York Times bestselling author Jacqueline Winspear, Maisie Dobbs investigates the murder of Indian immigrants in London. The year is 1933. Maisie Dobbs is contacted by an Indian gentleman who has come to England in the hopes of finding out who killed his sister two months ago. Scotland Yard failed to make any arrest in the case, and there is reason to believe they failed to conduct a thorough investigation. The case becomes even more challenging when another Indian woman is murdered just hours before a scheduled interview. Meanwhile, unfinished business from a previous case becomes a distraction, as does a new development in Maisie's personal life. Bringing a crucial chapter in the life and times of Maisie Dobbs to a close, Leaving Everything Most Loved marks a pivotal moment in this outstanding mystery series.